Threshold level of soil zine for optimum production of ginger (Zingiber officinale Rose.) - C K Thankamani, V Srinivasan, S Hamza, K S Krishnamurthy (Journal of Spices and Aromatic Crops, 2004)
A field experiment was conducted at Peruvannamuzhi (Kerala), for two years to evaluate the optimum level of zinc (Zn) content in soils for maximizing production of ginger (Zingiber officinale) on an Ustic Humitropept with varying levels of Zn fertilizer. The mean rhizome yield of two years was higher in plots where Zn @ 5 kg ha-1 was applied. A cubic model described satisfactorily the relationship between mean rhizome yield and fertilizer application rate. The optimum fertilizer dose for obtaining maximum rhizome yield was determined as 6 kg ha-1 of Zn. The maximum limit of soil DTPA-Zn for obtaining higher rhizome yield was 3.4 mg kg-1.